2013
DOI: 10.3382/ps.2012-02278
|View full text |Cite
|
Sign up to set email alerts
|

Valine needs in starting and growing Cobb (500) broilers

Abstract: Two independent experiments were conducted with male Cobb × Cobb 500 broilers to determine the optimal valine-to-digestible-lysine ratio for broiler development. We conducted a randomized block experiment with 7 treatments, each with 8 replicates of 25 starter birds (8 to 21 d of age) and 20 finisher (30 to 43 d of age) birds. To prevent any excess of digestible lysine, 93% of the recommended level of digestible lysine was used to evaluate the valine-to-lysine ratio. The utilized levels of dietary digestible l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 19 publications
2
28
1
2
Order By: Relevance
“…Accordingly, when evaluating lysine levels for broilers at different stages of creation, it is essential to consider its relationship with other essential amino acids. Among these, it is possible to highlight the methionine, threonine and valine, which are respectively the first, the third and the fourth limiting amino acid for broilers in diets formulated on vegetable ingredients (Corzo, Loar, & Kidd, 2009;Tavernari et al, 2013). In addition, when there is a non-balance of essential amino acids provided in the feed, even the non-essential amino acids may become limiting to the maximum expression of the birds genetic potential (Oliveira Neto & Oliveira, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, when evaluating lysine levels for broilers at different stages of creation, it is essential to consider its relationship with other essential amino acids. Among these, it is possible to highlight the methionine, threonine and valine, which are respectively the first, the third and the fourth limiting amino acid for broilers in diets formulated on vegetable ingredients (Corzo, Loar, & Kidd, 2009;Tavernari et al, 2013). In addition, when there is a non-balance of essential amino acids provided in the feed, even the non-essential amino acids may become limiting to the maximum expression of the birds genetic potential (Oliveira Neto & Oliveira, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Valine is a branchedchain amino acid that is mainly metabolized in the skeletal muscle, and it is responsible for body protein balance (Rogero & Tirapegui, 2008). Considering previous findings (Berres et al, 2011;Tavernari et al, 2013), it may be concluded that valine requirements for protein accretion are lower than those required for feed conversion in broilers. Therefore, the TID Val levels estimated for feed conversion ratio are recommended to be applied in broiler feed formulation, as they are (Table 4).…”
Section: Resultsmentioning
confidence: 93%
“…However, there was a quadratic effect (p≤0.05) of TID Val levels on breast yield, with the highest value estimated at 0.826% of TID Val ( Figure 5). Tavernari et al (2013) estimated 0.730% TID Val for 30-to 43-old broilers fed diets containing animal by products in order to obtain maximum breast yield. The higher estimated level of TID Val the present (0.826%) compared with that of Tavernari et al (2013) may be ascribed to the dietary inclusion of only plant-derived products, which may increase valine requirements in reduced-protein diets (Berres et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations